Variation of Conjunctival Vessel Width in Type-2 Diabetes Mellitus Patients - Sharma, Dr. Rishi; Gurunadh, Dr. V.S.; Jha, Dr. Ashok; Singh, Dr. Sonal (International Journal of Innovative Research in Medical Science, 2017)
Background: Diabetes mellitus (DM) refers to a group of common metabolic disorders that share the phenotype of hyperglycemia. Every part of the eye from conjunctiva to the optic nerve has manifestations secondary to diabetes mellitus which have been well documented and studied. Evaluation of conjunctival angiopathy associated with diabetes may help in detecting changes in the retina more easily and even by paraclinical workers. Methods: A cross-sectional, prospective study involving 70 patients of diabetes mellitus with disease duration of 15 to 19 years and equal number of age and sex matched controls were subjected to evaluation of conjunctival vessel width using the Appasamy anterior segment imaging system. Results: In the study population average conjunctival vessel width was 36μ and median width was 31.51 μ which was statistically different from the average width of 28.7 μ and median of 29 μ in controls[p <0.002]. In patients with diabetes mellitus there was an increase in the calibre of conjunctival vessels which increased significantly with increasing severity of DR [p < 0.0001]. Macrovessel dilation associated with diabetes may result in vessel engorgement and straightening, especially among those with longer duration of disease. Increased tortuosity associated with diabetes among conjunctival capillaries mirrors established vessel changes observed in the retina. Conclusion: There is variation in the conjunctival vessel width in diabetic patients compared with the normal population.